Exploring e-learning adoption in nurse education: a socio-cultural case study using Q and Bourdieu - Petit dit Dariel, Odessa (2011)
This research study employed Q-methodology (Q) to explore the factors influencing e-learning adoption in a nurse education context, and Bourdieu’s Theory of Practice (TOP) to analyse these findings using a case study of one school of nursing in the UK. E-learning adoption has been limited in nurse education despite a wide body of literature promoting its use for improved learning outcomes. Most research studies to date have used surveys to explore the overarching factors influencing academics to adopt e-learning across higher education more generally, but these findings have not identified the underlying issues influencing their responses to these factors, nor do they allow a deep analysis of discipline-specific factors.